Determining the antioxidant compounds of beer - Alexa, Loránd; Kántor, Andrea; Kovács, Béla; Czipa, Nikolett (Acta Agraria Debreceniensis, 2018)
The increasing consumption of beer indicates the necessity of the thorough analysis of its composition. In this study, the total phenolic content, flavonoid content and colour intensity of 24 beer samples have been determined. The samples contained pale barley, dark barley, pale wheat and dark wheat beers. The aim of the study was to determine the amount of the antioxidant compounds in beer, as well as to find correlation between different beer types and the above mentioned parameters. Dark barley samples contained phenolic compounds in the highest concentrations, and it can also be concluded that dark beers contain phenolic compounds and flavonoids in higher concentrations than pale beers in the case of barley and wheat samples. According to the performed statistical analysis, these beer types cannot be differentiated based on the analysed parameters. The highest percentage of correctly classified samples could be observed in case of dark barley samples, but this value has only been 75%, and the total result of correctly classified cases was only 41.7%. The analysis of more samples and parameters is required to carry out a successful differentiation.